Growth and morpho-physiology of Tectona philippinensis under different water stress and soil conditions (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Hernandez JO, Tolentino CA, Quiñones LAE, Villancio GB, Maldia LSJ, Combalicer MS. 2021. Growth and morpho-physiology of Tectona philippinensis under different water stress and soil conditions. Biodiversitas 23: 507-513. Plants exhibit adaptive mechanisms to respond to fluctuating amounts of soil moisture and poor soil properties; however, these mechanisms remain largely unknown in many forest tree species growing in dry and limestone areas in the Philippines, such as the endemic and endangered Tectona philippinensis Benth & Hook.f. This study investigated the growth and morpho-physiological responses of T. philippinensis wildlings to water stress and soil types. One-year-old wildlings were subjected to two watering treatments, i.e., well-watered and water-stressed, and three different soil types, i.e., Lobo, Batangas, Mt. Makiling Forest Reserve, and UP-Laguna-Quezon Land Grant. The root collar diameter, height, biomass allocations, and morpho-physiological traits (photosynthesis, stomatal conductance, transpiration, relative water content, specific leaf area, and stem green density) were measured. Overall, the growth performance of the wildlings was improved significantly when grown in soil from the natural habitat under WW conditions. Therefore, the recommended conservation approach potentially suitable for T. philippinensis is in-situ, particularly in riparian areas, when artificial irrigation is not possible and practical. The present study's findings provide us with a better understanding of the growth and ecophysiology of T. philippinensis under water-deficient conditions for its effective in-situ conservation.